The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.drugalcdep.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Sexual-orientation differences in drinking patterns and use of drinking contexts among college students

Abstract: Background Evidence suggests there are important sexual-orientation differences in alcohol consumption, particularly among women. Little is known about where gay/lesbian and bisexual college students drink or differences in patterns of alcohol use between heterosexual, gay/lesbian, and bisexual students. The goal of this analysis was to examine patterns of alcohol consumption—including drinking prevalence, quantity, frequency, and contexts of use—by sexual orientation. Methods Data on sexual identity, gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 60 publications
(124 reference statements)
3
30
0
Order By: Relevance
“…In fact, lesbian participants were the most likely to report heavy drinking, at twice the rates of bisexual and four times the rate of heterosexual women. These findings are consistent with those of other studies, including those employing random samples (Gruskin & Gordon, 2006;Coulter et al, 2016). It was also expected that women with exclusively same-sex sexual partners or both male and female sexual partners would report more heavy drinking that peers who had only male partners.…”
Section: Risk For Infertility As Function Of Sexual Identity Sexual supporting
confidence: 90%
See 1 more Smart Citation
“…In fact, lesbian participants were the most likely to report heavy drinking, at twice the rates of bisexual and four times the rate of heterosexual women. These findings are consistent with those of other studies, including those employing random samples (Gruskin & Gordon, 2006;Coulter et al, 2016). It was also expected that women with exclusively same-sex sexual partners or both male and female sexual partners would report more heavy drinking that peers who had only male partners.…”
Section: Risk For Infertility As Function Of Sexual Identity Sexual supporting
confidence: 90%
“…Researchers analyzing data from a large sample of college students found that, compared to their heterosexual peers, lesbian and bisexual women were more likely to be drinkers, as well as more likely to binge drink (Coulter, Marzell, Saltz, Stall, & Mair, 2016). A random sample of adult Californians also found that sexual minority women were twice as likely as heterosexual peers to RISK FOR INFERTILITY AS FUNCTION OF SEXUAL IDENTITY, SEXUAL BEHAVIOR, AND RACE AMONG U.S. WOMEN 23 be heavy drinkers (Gruskin & Gordon, 2006).…”
Section: Risk For Infertility As Function Of Sexual Identity Sexual mentioning
confidence: 99%
“…Coulter et al (2016) also found that lesbian college students reported drinking more often in bars compared to bisexual women. However, they statistically compared lesbians and bisexual women to heterosexual women rather than comparing lesbians and bisexual women to each other.…”
Section: Discussionmentioning
confidence: 82%
“…Further, reliance on bars to socialize is also associated with heavier drinking among lesbians (Heffernan, 1998). In contrast, among college students there is evidence that lesbians drink less often at fraternity/sorority houses and off-campus parties compared to heterosexual women, while bisexual women drink less often at fraternity/sorority houses and bars/restaurants compared to heterosexual women (Coulter, Marzell, Saltz, Stall, & Mair, 2016). While these studies provide a foundation for understanding where SMW drink, a comprehensive understanding of drinking context is necessary to inform prevention and intervention efforts.…”
Section: Introductionmentioning
confidence: 99%
“…While previous research on drinking among YMSM has emphasized the role of drinking as a way to escape negative feelings about one’s sexual orientation, the current findings suggest that an important motivation for drinking among YMSM is to feel good and to have fun. Drinking to have fun may be particularly likely to escalate into problematic drinking in this population, given evidence that gay men drink more frequently in bars compared to heterosexual men (42, 43), sexual minorities report more tolerant substance use norms compared to heterosexuals (44), and substance use norms (e.g., perceptions of drinking as normative, tolerance of heavy drinking and illicit drug use) are associated with greater substance use among sexual minorities (45). As such, drinking to enhance pleasure may remain an important predictor of alcohol use and problems for YMSM, given the unique aspects of drinking in this population.…”
Section: Discussionmentioning
confidence: 99%